2017
DOI: 10.2147/jbm.s136060
|View full text |Cite
|
Sign up to set email alerts
|

Identification of people with acquired hemophilia in a large electronic health record database

Abstract: BackgroundElectronic health records (EHRs) can provide insights into diagnoses, treatment patterns, and clinical outcomes. Acquired hemophilia (AH) is an ultrarare bleeding disorder characterized by factor VIII inhibiting autoantibodies.AimTo identify patients with AH using an EHR database.MethodsRecords were accessed from a large EHR database (Humedica) between January 1, 2007 and July 31, 2013. Broad selection criteria were applied using the International Classification of Diseases, Ninth Revision, clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…erefore, developing big data-driven intelligent algorithms that automatically learn massive information from medical record pathological sections and image data to provide guidance for diagnosis and disease treatment and establish different disease models have become more crucial in the era of intelligent healthcare than in the past [28][29][30]. By extracting and structuring ICD-11-coded data and utilizing expert knowledge, such as ICD-11 and SNOMED CT, the algorithm with the use of ICD-11 could hold potential value for solving critical healthcare problems that cannot be solved by traditional ICD-10.…”
Section: Discussionmentioning
confidence: 99%
“…erefore, developing big data-driven intelligent algorithms that automatically learn massive information from medical record pathological sections and image data to provide guidance for diagnosis and disease treatment and establish different disease models have become more crucial in the era of intelligent healthcare than in the past [28][29][30]. By extracting and structuring ICD-11-coded data and utilizing expert knowledge, such as ICD-11 and SNOMED CT, the algorithm with the use of ICD-11 could hold potential value for solving critical healthcare problems that cannot be solved by traditional ICD-10.…”
Section: Discussionmentioning
confidence: 99%
“…Validation study is useful for assessing these biases, but MDV data is anonymized and difficult to trace back to the original data. To maximize the validity of definitions in this study, definitions validated in the previous report [ 27 ] and constructed in consultation with clinicians were used.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier diagnosis of patients with chronic diseases such as multiple sclerosis and celiac disease was facilitated in the absence of diagnostic code data [ 30 , 31 ], and patients with asthma experiencing allergic bronchopulmonary aspergillosis as a disease exacerbation were accurately identified despite the lack of a specific code [ 32 ]. Additionally, 2 studies that aimed to identify patients with either congenital or acquired hemophilia found potentially high numbers of false-positive identifications when using diagnostic codes alone [ 33 , 34 ]. The current study further adds to a body of evidence illustrating the value of using unstructured data, and it is the first to demonstrate utility in HAE, a rare and debilitating disease for which more efficient diagnosis and effective management are needed.…”
Section: Discussionmentioning
confidence: 99%